Mycophenolate Mofetil in the Treatment of Steroid-Dependent or Frequently Relapsing Nephrotic Syndrome in Children: A Meta-Analysis - Xiang, Xin (Front Pediatr, 2021)
Objectives: This meta-analysis aims to evaluate the efficacy and safety of the mycophenolate mofetil (MMF) in the treatment of steroid-dependent nephrotic syndrome (SDNS) or frequently relapsing nephrotic syndrome (FRNS) in children. Methods: We searched for the studies especially the randomized controlled trials in PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure, and Wan Fang database. The data were analyzed by Review Manager 5.3 software. We used the GRADE pro-Guideline Development Tool online software to evaluate the quality of evidence. Results: Finally, we identified 620 studies, of which we included five randomized controlled trials and one prospective cohort study with 447 children. The results showed the following: (1) the relapse-free survival rate within 1 year—the MMF group was superior to the levamisole group [ratio difference (RD) = 0.13, 95% CI (0.02, 0.24), P = 0.02] but not to the calcineurin inhibitors (CNIs) group [RD = −0.27, 95%CI (−0.40, −0.14), P < 0.0001]; (2) the number of relapses within 1 year—the MMF group was less than that in the CNIs and levamisole group [mean difference (MD) = −0.26, 95%CI (−0.45, −0.08), P = 0.005]; (3) the cumulative prednisone dosage—the MMF group was lower than that in the control group [standardized mean difference (SMD) = −0.32, 95%CI (−0.53, −0.11), P = 0.003]; (4) incidence of adverse reactions—there was no significant difference between the MMF group and the control group [RD = 0.02, 95%CI (−0.04, 0.09), P = 0.46]. Conclusion: The therapy of mycophenolate mofetil in the treatment of SDNS or FRNS in children has a certain advantage in reducing the number of relapses and cumulative prednisone dosage within 1 year when compared with the CNIs and levamisole. However, due to the limited quantity and quality of the included studies, the conclusions above need to be confirmed by more high-quality randomized controlled trials.